2019
DOI: 10.1002/cbic.201900071
|View full text |Cite
|
Sign up to set email alerts
|

A FRET‐Based Near‐Infrared Fluorescent Probe for Ratiometric Detection of Cysteine in Mitochondria

Abstract: We report a near‐infrared fluorescent probe A for the ratiometric detection of cysteine based on FRET from a coumarin donor to a near‐infrared rhodamine acceptor. Upon addition of cysteine, the coumarin fluorescence increased dramatically up to 18‐fold and the fluorescence of the rhodamine acceptor decreased moderately by 45 % under excitation of the coumarin unit. Probe A has been used to detect cysteine concentration changes in live cells ratiometrically and to visualize fluctuations in cysteine concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
(23 reference statements)
0
8
0
1
Order By: Relevance
“…Liu et al , in 2019, reported FRET-based ratiometric red-emitting fluorescent probe 11 which is based on the strategy of combining rhodamine with coumarin as a whole fluorophore. 44 Probe 11 used coumarin as the energy donor, rhodamine as the energy receptor, piperazine as the spacer linker and trifluoromethylphenyl thiester as the recognition group of biothiols. In the PBS/EtOH (V/V = 7/3, pH = 7.4) mixed system, the fluorescence emission of probe 11 was decreased at 467 nm (the emission wavelength of the coumarin part) and increased at 645 nm (the emission wavelength of rhodamine part) due to the effect of FRET.…”
Section: Red-emitting/near-infrared Biothiol Fluorescent Probes Based...mentioning
confidence: 99%
“…Liu et al , in 2019, reported FRET-based ratiometric red-emitting fluorescent probe 11 which is based on the strategy of combining rhodamine with coumarin as a whole fluorophore. 44 Probe 11 used coumarin as the energy donor, rhodamine as the energy receptor, piperazine as the spacer linker and trifluoromethylphenyl thiester as the recognition group of biothiols. In the PBS/EtOH (V/V = 7/3, pH = 7.4) mixed system, the fluorescence emission of probe 11 was decreased at 467 nm (the emission wavelength of the coumarin part) and increased at 645 nm (the emission wavelength of rhodamine part) due to the effect of FRET.…”
Section: Red-emitting/near-infrared Biothiol Fluorescent Probes Based...mentioning
confidence: 99%
“…Surgery is mostly guided by the surgeon's perception of the tissue under optically visible light. Fluorescence-guided surgery is a relatively new field, which could be added to the surgeon's armamentum, providing additional information about the anatomy, physiology and pathology of the patient intraoperatively [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many fluorescent probes for biothiol detection have been developed with different sensing mechanisms [3b,4] . These include photo‐induced electron transfers, [4a,b,j,5] addition reactions with selectivity of glutathione over cysteine, [6] removal of a heavy atom fluorescence quenching effect by halogen nucleophilic substitution, [7] intramolecular charge transfer, [8] and FRET [4b,c,9] . Among these different sensing approaches, FRET‐based ratiometric fluorescent probes possess unique advantages with self‐calibration capabilities [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…These include photo‐induced electron transfers, [4a,b,j,5] addition reactions with selectivity of glutathione over cysteine, [6] removal of a heavy atom fluorescence quenching effect by halogen nucleophilic substitution, [7] intramolecular charge transfer, [8] and FRET [4b,c,9] . Among these different sensing approaches, FRET‐based ratiometric fluorescent probes possess unique advantages with self‐calibration capabilities [9,10] . Systematic errors, which are characteristic of intensity‐based fluorescent probes resulting from fluctuations in the excitation light source, sample heterogeneity, uneven dye distribution, variations, and compartmental localization, do not occur with ratiometric probes [10,11] .…”
Section: Introductionmentioning
confidence: 99%